Brand preference and its impacts on customer share of visits and word-of-mouth intention: an empirical study in the full-service restaurant segment - Hwang, Jinsoo (Kansas State University, 2011)
This study attempted to investigate antecedents and consequences of consumers’ utilitarian and hedonic attitudes toward restaurant brands and to examine the effects of brand prestige on brand preference and word-of-mouth intention with customer involvement as a moderator. In study 1, to investigate the antecedents and consequences of consumer attitudes toward restaurant brands in the full-service restaurant, this study proposed, based on existing theoretical premises, significant interrelationships among three service qualities (i.e., physical environment quality, interactional quality, and outcome quality). This study also hypothesized that these service qualities predict consumers’ utilitarian and hedonic attitudes toward restaurant brands. Finally, this study examined the effects of consumer attitudes toward restaurant brands in forming brand preference and relative customer share of visits. A theoretical model was proposed and then tested with data collected from 318 casual and 303 fine dining restaurant patrons. The results of data analysis indicated significant interrelationships among three service qualities in both casual and fine dining restaurants. In addition, interactional and outcome qualities had significant effects on utilitarian and hedonic attitudes toward restaurant brands in the casual dining restaurant. In the fine dining segment, interactional quality significantly influenced both utilitarian and hedonic attitudes toward restaurant brands, while physical environment and outcome qualities had positive impacts only on hedonic attitude toward the restaurant’s brand. Finally, utilitarian and hedonic attitudes toward restaurant brands enhanced brand preference, and in turn, brand preference increased relative customer share of visits in both casual and fine dining restaurants. The purpose of study 2 was to examine the effects of brand prestige on brand preference and word-of-mouth with customer involvement as a moderator in the fine dining restaurant segment. Based on a thorough literature review, this study hypothesized that brand prestige would have positive effects on brand preference and word-of-mouth and that brand preference would have a positive relationship with word-of-mouth. Finally, this study examined the moderating role of customer involvement in the relationships between (1) brand prestige and brand preference, (2) brand prestige and word-of-mouth, and (3) brand preference and word-of-mouth. A total of 293 questionnaire responses were used to empirically test the proposed relationships in fine dining restaurants. This study found that brand prestige has significant effects on brand preference and word-of-mouth. In addition, brand preference had a positive relationship with word-of-mouth. However, customer involvement as a moderator was not supported.
Keywords: Service quality; Customer attitudes; Brand preference; Relative customer share of visits; Brand prestige; Word-of-mouth; Marketing (0338)